(untitled) (Diametros, 2010)
The aim of the present paper is to reconsider Augustine’s role in the history of the concept of self. Our analysis is based on Charles Taylor’s account of the Augustinian inward turn. Taylor argues that Augustine’s project played a key role in the development of the modern notion of self, because the idea of "inward turn" led the thinker to give the idea of "self-reflexivity" a major position and made him the forefather of the Cartesian cogito. However, we think that it is inappropriate to take the notion of "self-reflexivity" as the essential component of the Augustinian inward turn. We argue that Augustine’s real contribution to the history of the notion of self is to be found in the "private" character of his idea of inward turn, and not in the notion of self-reflexivity. Hence, by comparing the differences between Augustine’s and Plotinus’ notions of "inward turn," we show how Augustine broke with the tradition and put forward a new understanding of inward turn.